Decomposition of intended use of IPO proceeds: Evidence from Malaysia - Badru, Bazeet Olayemi (Gadjah Mada International Journal of Business, 2021)
The main objective of the study is to identify what Malaysian IPO issuers indicate as intended use of IPO proceeds and the use that has the highest amount of allocation. In order to achieve the objective of the study, a manual content analysis of 221 IPO prospectuses issued during the period of 2005-2015 were considered. Based on the manual content analysis, the data were analysed using descriptive statistics and analysis of variance (ANOVA). The results indicate that the three major intended uses of IPO proceeds in Malaysian IPO market are growth opportunities (53.90%), debt repayment (29.12%) and working capital (12.87%). However, growth opportunities and debt repayment have greater amount of allocation than working capital over the sample periods. Additionally results show that Malaysian IPO issuers expend more on capital expenditure and expansion rather than research and development in terms of growth opportunities. Further analysis in terms of the frequencies of number of IPO issuers indicate that number of issuers that have a designated amount for working capital (95%) supersede issuers in the growth opportunities group (90%). These results suggest that issuers can consider intended use of IPO proceeds information as a signal mechanism and potential investors can as well consider the information useful before making their investment decisions.